Flexing Ethics in the Digital Age: Qur’anic Maqāṣidī Perspective from Al-Taḥrīr wa al-Tanwīr - Rifa Tsamrotus Saadah; Zaky Mumtaz Ali; Abur Hamdi Usman (ZAD Al-Mufassirin, 2026)
This study aims to examine the maqāṣidī exegesis critique of the flexing culture, with a particular focus on Muhammad Ṭāhir Ibn ‘Āshūr’s interpretation in Al-Taḥrīr wa al-Tanwīr. Employing a qualitative-descriptive approach and thematic exegesis method, the formal object of this research is the theory of maqāṣid al-Qur’ān, while the material object comprises Qur’anic verses relevant to flexing behavior. The scope of the study includes Surah al-Qashash (76–83), al-Ḥadīd (20), and other verses addressing prohibitions against isrāf, tabdhīr, and riyā’. The findings reveal that Ibn ‘Āshūr interprets the phenomenon of flexing as a deviation from the maqāṣid al-Qur’ān, which emphasize values of simplicity, qanā‘ah (contentment), and social responsibility. This maqāṣidī critique underscores that flexing negatively impacts Islamic character education by weakening the internalization of values such as zuhd (asceticism), ikhlāṣ (sincerity), and wasaṭiyyah (moderation) in moral development. The novelty of this study lies in positioning Qur’anic maqāṣidī exegesis as a critical framework for addressing contemporary digital culture, offering an integrative ethical foundation that connects classical tafsir with modern challenges of consumerism. This contribution enriches Islamic character education discourse by providing a Qur’anic-based alternative to counteract the ethical crisis of flexing in the digital era.